Implementing outcome based education using project based learning at University of Malaya - Hashim, Roslan; Mohd Din, M.A. (2009)
In this paper, the authors evaluated the implementation of a Project Based Learning (ProjBL) incorporating the development of students' soft skills as well as technical or professional competences. The research question addressed here is the suitability of ProjBL in achieving the desired learning outcomes i.e. practical knowledge of engineering surveying, basic knowledge on engineering design, and soft skills or personal competences. The objectives are two-fold; (i) to evaluate the effectiveness, and (ii) to identify potential improvement. The course, the Engineering Surveying Camp offered at Year-I of a four- year civil engineering degree programme, is a two-week field course. During the course, the students carried out an actual surveying and design project in groups of 6-7 students supervised by the academics. Assessment of technical aspects was based on daily output and final products while for soft skills on performance during the various sessions. Evaluation was carried out based on the outputs and student performance during the various sessions. It was found that the technical aspects were achievable though with lesser degree for the engineering design. On soft skills, students demonstrated an overall improvement of competency but it was difficult to ascertain the levels for the average students while the best and poor performers were easily observed.